Anak - Quintos, Rory B. (2001)
This is the story of a mother's agony and her desperate attempt to pieces back the broken fragments of her shattered family. Josie (Vilma Santos) returns to Manila after working as a Domestic Helper in Hongkong for ten years. Her beloved husband, Rudy (Joel Torre), who died five years ago, was good-natured, loving and kind but was not good providers. She was forced out of financial need to go abroad and slave under abusive employers in order to provide a better life for the family. But her happy expectation of a joyful reunion with her beloved children is dashed to pieces when she finds that her absences, her family has fallen apart: her first-born, Carla (Claudine Barreto) has run loose and wild for lack of guidance; her son Michael (Baron Geisler), is in deep trouble in school; and her youngest, Daday (Sheila Junsay), doesn't even know who she is. Josie is stranger to her own family, she tries to maintain a happy and cheerful exterior while desperately trying to reach out to her children but they continue to repel her tender appeals ironically, it is Daday, her youngest who grew up without knowing her, who first opens her own heart and embraces her into the family. Unkown to Josie, her two elder children harbor a deep and painful resentment toward her, In their minds, their motherdoes not care for them. She had left for abroad even when they cried and begged her not to, and she did not even bother to come home to be with them for their father's funeral. But Carla and Michael do not know their mother's side of the story. Josie was devastated upon hearing of Rudy's death but she had been unable to go home because her employers cruelty kept her locked inside the house. And she had endured another five years of hard labor knowing that her family would need money then, more than ever.
Josie's problems, despite all her desperate efforts, become worse and worse. She loses all of her savings in a failed business venture, MIchael iskicked out of school, and worst of all, Carla becomes pregnant by one of her lovers. Josie id horrible aggrieved when Carla, in a fit of helpless fury, throws at Josie's face all her years of pent-up anger and resentment. She blames Josie for her aimless, ruined life. Josie was never to give her love, she stays, that is why she seeks it in the arms of men. Finally, Josie admits defeat, she has failed bitterly in her role as a mother. What is right thing for her to do? Should she stay or should she go? Will she have the courage to try to reclaim her family, or will she take the easier way out and return to her familiar life in Hongkong.